The Influence of Human Resource Quality and Work Environment on Employee Performance with Promotions as Intervening Variables Binjai City Public Works and Spatial Planning Office - Hendra Sihotang; Muhammad Isa Indrawan (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This study aims to analyze the effect of the quality of human resources and work environment on employee performance with promotion as an intervening variable. The type of research used is associative quantitative. This research was conducted at the Public Works and Spatial Planning Office of the City of Binjai. The population in this study was 79 employees and 79 employees would be sampled using the saturated sample technique. The data source used is primary data and data collection is done by distributing questionnaires. The research model used is path analysis and the measurement tool uses Smart PLS VERSION 3.3.3. The results of his research are that the quality of human resources has a negative and insignificant effect on employee performance. The quality of Human Resources has a negative and insignificant effect on Promotion. Work Environment has a positive and significant effect on Employee Performance. The work environment has a positive and significant effect on promotion. Promotion has a positive and significant effect on employee performance. The quality of human resources has no significant negative effect on employee performance through promotion. The work environment has a positive and significant effect on employee performance through promotion.